The Effect of Facial Expressions on the Evaluation of Ambiguous Statements. Issue 3 (October 2015) - Meeten, Frances; Ivak, Peter; Dash, Suzanne R.; Knowles, Sam; Duka, Theodora; Scott, Ryan; Kaiser, Jakob; Davey, Graham C. L.
The present experiment adapted the "Voluntary Facial Action" (VFA) technique (Dimberg & Söderkvist, 2011) to study the effect of facial expressions on the interpretation of ambiguity. This required participants to react with either the zygomatic major muscles (smile) or the corrugator supercilii muscles (frown) when exposed to different stimuli, some of which were ambiguous statements. While contracting the required facial muscles, participants also rated each stimulus on a negative-positive scale. Results indicated that participants contracting smiling muscles during ambiguous statements rated those statements as significantly more positive than participants contracting frowning-relevant muscles. This effect remained significant in participants who were unaware of the purpose of the experiment, and unaware that the experiment was related to mood. Previous studies have demonstrated that facial expressions can reflect the valency of a bias in responding to ambiguous stimuli (e.g. Neta, Norris, & Whalen, 2009), but the present study goes further by suggesting that facial expressions can actively influence the interpretation of stimuli as complex as verbal statements. Some of the implications for the way in which facial expressions may influence cognitive processes relevant to psychopathology are discussed.